“No es mi madre la tierra” ‘The Earth Is Not My Mother’: Ecology in Gloria Fuertes’s Last Poetry - Douglas K. Benson (Studies in 20th & 21st Century Literature, 2012)
Since the 1930s, Gloria Fuertes’s poetry has attracted listeners and readers to her unique combination of verbal play, witty juxtapositions of erudite and popular sources, and uncanny linguistic virtuosity. Thirteen years after her death in 1998, her popularity continues to grow as new printings of her best-selling books and new editions of her early poetry appear in print. The last book over which she had editorial control, Mujer de verso en pecho (1995) ‘Woman with Verse on her Chest,’ is her most provocative, expanding considerably the thematic range to which she applied her unconventional poetic strategies. One previous thematic element which takes a new direction is that of ecological concerns, which her speakers call into question as they link them to other equally urgent ethical concerns such as poverty, hunger and war. These poems create startling and intellectually challenging contradictions for the reader that recall the Spanish Baroque, and yet cast them into wholly accessible language that defies the hermetic, elitist avant-garde and novísimos movements of the twentieth century.
Keywords: Gloria Fuertes; No es mi madre la tierra; poetry; poetic strategy; ecology; nontraditional literature